Transitioning to Green Maritime Transportation in Philippines - Palconit, E. V.; Abundo, M. L. S. (Engineering, Technology & Applied Science Research, 2019)
Philippine maritime industry is considered as a vital component in achieving inclusive growth and socio-economic progress. Philippines has been known as one of the susceptible to the impact of climate change countries, and generally the changing climate hampers its economic development. The government committed to reduce carbon emissions to 70% by 2030 during the 2015 Paris climate conference. This study aims to map the potential sites and vessels for electric ferry operation for transitioning to green maritime transportation in Philippines. At present there are 83 ports and 110 ferries in the country with 33670 registered vessels as of December 2017. It was identified that the 9201 vessels with 10≥GRT≥3 will be used for electrification as a kickoff in implementing electric ferry since these vessels are feasible for retrofitting the electric system. Implementing green energy sources in the country’s marine transportation will reduce CO2 emission by 22.09% in the transport sector.